It's not time to make a change: Sovereign fragility and the corporate credit risk - Fabio Fornari; Andrea Zaghini (Goethe University Frankfurt, Center for Financial Studies (CFS), 2021)
Relying on a perspective borrowed from monetary policy announcements and introducing an econometric twist in the traditional event study analysis, we doc- ument the existence of an "event risk transfer", namely a significant credit risk transmission from the sovereign to the corporate sector after a sovereign rating downgrade. We find that after the delivery of the downgrade, corporate CDS spreads rise by 36% per annum and there is a widespread contagion across coun- tries, in particular among those which were most exposed to the sovereign debt crisis. This effect exists on top of the standard relation between sovereign and corporate credit risk.
urn:nbn:de:hebis:30:3-573904
Keywords: G15; G32; G38; 330; sovereign rating; corporate credit risk; CDS spreads